Feeding of glucomannans and anthocyanins combination in the containing microparticle protein on fat digestibility and fat deposition on broiler chicken - Lilik Krismiyanto; Nyoman Suthama; Mulyono Mulyono; Masrifah Ayu Ningrum (Universitas PGRI Semarang, 2022)
This study aims to evaluate the effects of combination of glucomannan and anthocyanin in feeds containing protein microparticles on fat digestibility and fat deposition in broiler chickens. The 216 healthy 7-day-old broiler chicks strain CP 707 was used with treatment of glucomannan from porang tuber extract and anthocyanins from purple sweet potato extract. The study was arranged by a completely randomized design (CRD) with a factorial pattern with treatment consisting of 2 factors (A and B). In A, there were 3 glucomannan treatments, A1 (0%), A2 (0.05%) and A3 (0.1%), while in B contained 3 anthocyanin treatments, B1 (0), B2 (0.07%) and B3 (0.14%) with 3 replications. The measure was fat digestibility, precentage of abdominal fat and meat fat mass. The data were analyzed for variance at the 5% level and continued with Duncan's double test at the 5% level. The results showed that the addition of a combination of glucomannan and anthocyanin in the feed containing protein microparticles had an interaction (P<0.05) on fat digestibility, meat fat mass and relative weight of abdominal fat in broiler chickens. The addition of a combination of 0.1% glucomannan and 0.14% anthocyanin (A3B3) in the feed containing microparticle protein was able to reduce fat digestibility, relative abdominal fat weight and meat fat mass in broiler chickens.